NIHR Clinical Research Networks: what they do and how they help paediatric research. Issue 8 (17th January 2017) - Lythgoe, Hanna; Price, Victoria; Poustie, Vanessa; Attar, Sabah; Hawcutt, Daniel; Preston, Jennifer; Beresford, Michael W
Abstract : This review provides paediatricians with an update on the new structure of the National Institute for Health Research's (NIHR) Clinical Research Network (CRN): Children and its role within the wider NIHR infrastructure. The network supports delivery of high-quality research within the NHS in England and supports researchers, through provision of staff and resources, with feasibility, site set-up, patient recruitment and study management. Since 2013, over 80% of commercial contract studies running within the UK sat within the UKCRN Portfolio. Of the diverse, increasing portfolio of studies supported by the network, many studies are interventional, with 33% being randomised controlled studies. Recruitment to studies supported by the network through the Children's Portfolio has consistently improved. Over 200 000 participants have been recruited to the Children's Portfolio studies to date, and there are currently approximately 500 studies open to recruitment. The CRN: Children has successfully involved patients and the public in all aspects of study design and delivery, including through the work of Generation R. Challenges remain in conducting paediatric research and the network is committed to supporting Children's research and further building on its achievements to date. Education and engagement of paediatricians within the network and research is important to further improving quality and delivery of paediatric research.